International Review of Leave Policies and Related Research, 2007 - Alexander, M; Brennan, D; Whitehouse, G (Department of Business, Enterprise and Regulatory Reform, 2007)
This report is produced by an international network on leave policy and research, consisting of over 40 experts from 23 countries, mostly in Europe. The network covers policies for parents and others with care responsibilities, including for adult relatives, as well as policies available to the whole population such as life course career breaks and time accounts. But initially, priority is being given to leave policies focused on the care of children. Among the purposes of this network are: the exchange of information about policies, both in individual countries and by international organisations, and research on leave policies; the provision of a forum for the cross-national discussion of issues and trends in policy and research; and provision of a source of regularly updated information on policies and research.
Employment Relations Research Series No. 80
Australia: Country note on leave policies and research
Keywords: Employment -- Conditions; Employment; Policy; Government, law and policy; Labour market; Policy; Employment; Conditions; Government, law and policy; Employment and unemployment